Exploring the long‐term psychosocial impact of paediatric haematopoietic stem cell transplantation for nonmalignant diseases - Joëll E. Bense; Lieke terWelle; Hilda Mekelenkamp; Marieke Schimmel; Marloes Louwerens; Arjan C. Lankester; Arwen H. Pieterse; Anne P. J. dePagter (Wiley, 2022)
Abstract Introduction An understanding of the long‐term psychosocial impact of paediatric haematopoietic stem cell transplantation (HSCT) for nonmalignant diseases is needed to optimize pre‐HSCT counselling, supportive care and long‐term follow‐up programmes after HSCT for this group of patients and caregivers. Methods This qualitative study included 14 patients who underwent transplantation for a nonmalignant disease during childhood. In‐depth interviews were held online to explore patients' perspectives on the long‐term psychosocial impact of HSCT on their lives. The results were analysed based on the Grounded Theory approach. Results Patients' median age at the time of the interview was 19 years (range: 14-49), and the median years after HSCT was 12 years (range: 3-33). Four main themes were identified: (1) doing okay, (2) experiencing persistent involvement with healthcare services, (3) influence on relationships with loved ones and (4) impact on the patient's life course. Subthemes extracted were doing okay, feeling of being cured, health limitations, sense of vulnerability, ongoing connection to the hospital, acceptance, friendship, family relations, development of own identity, not taking life for granted, social development, impact on (school) career and thinking about the future. Conclusions Patients reported active coping strategies and resilience after this high‐impact treatment. The data highlight the need for patient‐adjusted supportive care, indicating more need for supportive care in the long‐term outpatient clinic. Patient Contribution This study included patients as participants. Caregivers were approached if patients were below a certain age. Additionally, preliminary results were presented during a patient conference day.